2018
DOI: 10.3390/su10040959
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Valuation of Change in the Quality of Rural Tourism Resources: Choice Experiment Approaches

Abstract: This study examined tourists' preferences for the change in the quality of rural tourism resources in Korea. This study measured tourists' satisfaction levels about their recent tourism experience in a stated preference mechanism to estimate the economic value of qualitative improvement associated with tourism resources. Using a pivot-style experimental design approach in developing the choice experiment, this study estimated econometric models that allow for flexible structures in error components of the util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Similar findings are reported in Haralambopoulos and Pizam's [17] study in Samos (Greece). Furthermore, previous studies have identified a positive linkage between residents' job sector/economic dependence and their perceptions of tourism [17,[21][22][23][24]. Those who benefit economically from tourism often view its impacts more positively [12] and are less likely than others to report its negative impacts [25].…”
Section: Resident Perceptions Of Tourism Impacts and Demographic Varimentioning
confidence: 99%
“…Similar findings are reported in Haralambopoulos and Pizam's [17] study in Samos (Greece). Furthermore, previous studies have identified a positive linkage between residents' job sector/economic dependence and their perceptions of tourism [17,[21][22][23][24]. Those who benefit economically from tourism often view its impacts more positively [12] and are less likely than others to report its negative impacts [25].…”
Section: Resident Perceptions Of Tourism Impacts and Demographic Varimentioning
confidence: 99%
“…The most common attributes considered in choice experiments applied to rural tourism studies are price (Hearne and Salinas 2002;Hearne and Santos 2005;Albaladejo-Pina and Díaz-Delfa 2009;Scarpa et al 2011;Chaminuka et al 2012), infrastructure, type of building or diverse facilities (Hearne and Salinas 2002;Díaz-Delfa 2005, 2009), location (Hearne and Salinas 2002;Albaladejo-Pina and Díaz-Delfa 2005, https://doi.org/10.17221/56/2021-AGRICECON 2009), experiences related to farming Díaz-Delfa 2005, 2009), craft activities (Chaminuka et al 2012), landscape/diversity (Scarpa et al 2011) or local festivals (Kim 2018), information type (Hearne and Salinas 2002;Hearne and Santos 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nevertheless, today's tourists are becoming ever more difficult to describe simply in terms of their socio-demographic and trip characteristics [4][5][6], especially under the circumstance that most of the destinations offer a range of tourism products, facilities, and services to attract tourists. On the other hand, from the view point of the competitiveness of a destination, it is critical to explore the evaluative factors influencing the destination choices of the tourists and understand how they behave when selecting a destination [7][8][9][10][11]. Due to the characteristics of feasibility, generalization, and reasonability, tourist motivation-as one of the specific segmentation variables-is extensively applied in segmenting markets for destinations.…”
Section: Introductionmentioning
confidence: 99%